2008
DOI: 10.1074/jbc.m706937200
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Binding and Cdk5 Phosphorylation of p35 Regulate Its Effect on Microtubules

Abstract: In the nervous system, Cdk5 and its neuronal activator p35 are involved in the control of various activities, including neuronal differentiation and migration. Recently, we have reported that p35 is a microtubule-associated protein that regulates microtubule dynamics ( 2؉ -specific manner, suggesting that p35 may be involved in the Ca 2؉ /CaMmediated inhibition of microtubule assembly. Second, p35 phosphorylation by Cdk5 interferes with the microtubule-binding and polymerizing activities of p35. Using a mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…The p10 interaction in vivo with other cellular proteins, such as tubulin (microtubules) and calmodulin (31,74), may protect the activity of the Cdk5-p35 complex (and not the Cdk5-p25 complex) from p5 inhibition. In our experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The p10 interaction in vivo with other cellular proteins, such as tubulin (microtubules) and calmodulin (31,74), may protect the activity of the Cdk5-p35 complex (and not the Cdk5-p25 complex) from p5 inhibition. In our experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this kind of regulation has already been observed for the microtubule-associated protein p35, which is also regulated by site-specific phosphorylations and Ca 2ϩ -CaM with MT overlapping binding sites (41). Similar mechanisms of CaM regulation were again suggested for Tau (42)(43)(44).…”
Section: Map6(90 -177) Binds and Stabilizesmentioning
confidence: 59%
“…The situation in cells, with numerous interacting proteins, differs fundamentally, however. It has been demonstrated that p35, with its p10 N-terminal "domain" interacts with other proteins such as microtubules, actin, munc18 and others forming a multimeric complex [6,7,31,33,34]. We suggest that binding of macromolecules to the p10 domain favors a p35 conformational change such that it competes successfully for the Cdk5 catalytic site and sustains activity.…”
Section: P35-derived Peptides As Therapeutic Candidates For Neurodegementioning
confidence: 96%
“…In the brain, expression of p35 and p39 increases with development till adult; in fetus and adult p35 is phosphorylated by Cdk5 at Ser 8 which localizes a cytoplasmic Cdk5/p35 whereas in the fetus, phosphorylation of tyrosine 138 by tyrosine kinases, results in degradation of p35 via the proteosomeubiquitin pathway [4]. In the adult, however, Cdk5/p35 is restively more stable since neither site is phosphorylated as p35 acts to bundle microtubules and actin [6,7]. These regulatory options have profound effects on the role of Cdk5 in health and disease [8][9][10][11] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation